ANALYSIS THE INFLUENCE OF PHYSICAL WORK ENVIRONMENT AND NON-PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY IN GENERAL HOSPITAL GMIM KALOORAN AMURANG SOUTH MINAHASA REGENCY - Joseph, Intan (Jurnal Berkala Ilmiah Efisiensi, 2016)
Hospital Kalooran Amurang South Minahasa Regency is a private organization engaged in the field of health care in South Minahasa regency, North Sulawesi Province. The dynamics of the problems encountered in the field of public health is likely to continue to grow. Therefore the Hospital Kalooran Amurang have to work hard, in order to carry out the health care function optimally. Employee productivity is one aspect that should get the attention of the leadership Hospital Amurang Kalooran South Minahasa District. Through effective work, the cure rate of patients treated will be higher. Which in turn will improve the quality of people's lives, and have an impact on the reputation and public confidence in the Hospital. This research objective is to analyze the influence of the physical work environment and non-physical work environment on employee productivity in General Hospital GMIM Kalooran Amurang South Minahasa regency simultaneously and partially. The population of this research is all employee in General Hospital GMIM Kalooran Amurang South Minahasa. By using a purposing sampling method, this research sample is 54 employee as a respondent. Using a Multiple Regression as a analysis tool, this research found that there is a significant influence of the physical work environment and non-physical work environment on employee productivity in General Hospital GMIM Kalooran Amurang South Minahasa regency simultaneously and partially.